Mesin Produksi Sebagai Upaya Peningkatan Produktivitas di UKM Mamabon - Edo Rantou Wijaya; Khairul Akli; Nofan Hadi Ahmad; Ari Pranata Primisa Purba; Rizki Fadhillah Lubis (Journal of Industrial Community Empowerment, 2022)
Productivity is needed to compete in the modern retail market which requires the right product at the right time and in the right quantity. This activity aims to increase productivity in Small and Medium Enterprises, one of which is Mamabon. Mamabon SMEs have not been able to fully meet the target market due to limited production capacity so they need machines to increase production. The stages of this activity are in the form of surveys to partner locations, choosing alternative solutions, implementing and evaluating activities. Based on the results of the activity evaluation, the procurement of production machines in this activity was successful in increasing productivity by increasing production capacity by 66.6%, shortening production time and stages.